2010
DOI: 10.1677/erc-09-0106
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear export and mitochondrial and endoplasmic reticulum localization of IGF-binding protein 3 regulate its apoptotic properties

Abstract: Tumor suppression by IGF-binding protein 3 (IGFBP3) may occur in an IGF-independent manner, in addition to its role as a regulator of IGF bioavailability. After secretion, IGFBP3 is internalized, rapidly localized to the nucleus, and is later detected in the cytoplasm. We identified a putative nuclear export sequence (NES) in IGFBP3 between amino acids 217 and 228, analogous to the leucine-rich NES sequence of p53 and HIV Rev. Mutation of the NES prevents nucleocytoplasmic shuttling of IGFBP3 and blocks its ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…The importance of these interactions was suggested by the loss of IGFBP-3-induced apoptosis in Nur77-deficient cells. As noted earlier, mutation of a putative CRM1-binding NES motif on IGFBP-3 also prevented IGFBP-3-induced apoptosis, and also resulted in increased nuclear RXRα-Nur77 retention (Paharkova-Vatchkova and Lee, 2010). Together these date indicate a role for nuclear IGFBP-3 in the CRM1-mediated export of RXRα-Nur77 complexes during IGFBP-3-mediated apoptosis in prostate cancer cells.…”
Section: Igfbp-3 and Nuclear Receptorsmentioning
confidence: 64%
See 2 more Smart Citations
“…The importance of these interactions was suggested by the loss of IGFBP-3-induced apoptosis in Nur77-deficient cells. As noted earlier, mutation of a putative CRM1-binding NES motif on IGFBP-3 also prevented IGFBP-3-induced apoptosis, and also resulted in increased nuclear RXRα-Nur77 retention (Paharkova-Vatchkova and Lee, 2010). Together these date indicate a role for nuclear IGFBP-3 in the CRM1-mediated export of RXRα-Nur77 complexes during IGFBP-3-mediated apoptosis in prostate cancer cells.…”
Section: Igfbp-3 and Nuclear Receptorsmentioning
confidence: 64%
“…The IGFBP-3 sequence includes several putative NES motifs in its central and C-terminal domains. One such motif, starting at Met190 (excluding the signal peptide) has been reported to serve as a functional NES (Paharkova-Vatchkova and Lee, 2010). In fact this sequence overlaps another putative NES starting at Leu194 (Figure 1).…”
Section: Nuclear Import and Export Of Igfbp-3mentioning
confidence: 99%
See 1 more Smart Citation
“…When we examined the IGFBP3 mRNA expression level in 231Br cells, we found that it is expressed 25-30 fold more than in 231P (Figure 2A). While IGFBP3 is traditionally studied as a secreted protein, it is known to carry out some of its functions intracellularly [38,39]. We first analyzed the levels of secreted IGFBP3 by collecting the conditioned medium of 231P and 231Br cells.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular mechanisms underlying these effects in CaP cells include rapid cellular internalization via Caveolin-1 binding and nuclear localization (40,41); and activation of the intrinsic apoptosis pathway via association with the nuclear receptors RXRα and Nur77 and nuclear export with subsequent mitochondrial translocation (39,42,43). Importantly, we have established an important physiologic role for IGFBP-3 in apoptosis induced by androgen-deprivation.…”
Section: Discussionmentioning
confidence: 75%